Field efficacy of some insecticides against whitefly infesting mulberry, Morus alba L. (The Journal of Plant Protection Sciences, 2021)
The  whitefly,  Dialeupora  decempuncta   it was felt necessary to study the field efficacy of Q u a i n t a n c e & B a k e r ( H o m o p t e r a : these insecticides against Dialeuropora Aleyrodidae), is a polyphagous pest, started decempuncta.causing  severe  damage  to  mulberry  Morus  The  experiment  was  conducted   at   Central alba L since 1994. They suck leaf sap causing Sericultural Research & Training Institute, chlorosis, dryness of leaves, leaf curl and sooty Berhampore, West Bengal during August to mould disease and give effect to a culminating November 2009.
Keywords: culminating; polyphagous pest; chlorosis